The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/su14084569
|View full text |Cite
|
Sign up to set email alerts
|

Safety-Management Practices and the Occurrence of Occupational Accidents: Assessing the Mediating Role of Safety Compliance

Abstract: This study examines the impact of critical safety-management practices on the occurrence of occupational accidents by means of safety compliance in Malaysia’s oil and gas industry. This study employed a cross-sectional design, in which data were collected from oil and gas downstream operations in five states within Malaysia using the convenience-sampling technique. The valid data of 280 responses were analyzed with Smart-PLS, and the structural-equation-modeling technique was applied. The study’s outcome revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 85 publications
1
13
0
3
Order By: Relevance
“…(ii) SEM perform well, particularly for complicated models with several indicators and latent variables [ 66 ]. Thus, SEM is now widely employed in various fields of social science investigation, such as hospitality management [ 67 ], the construction industry [ 68 , 69 ], the petroleum industry [ 70 ], commercial aviation [ 71 ], education [ 72 ], safety and health [ 73 , 74 ].…”
Section: Methodsmentioning
confidence: 99%
“…(ii) SEM perform well, particularly for complicated models with several indicators and latent variables [ 66 ]. Thus, SEM is now widely employed in various fields of social science investigation, such as hospitality management [ 67 ], the construction industry [ 68 , 69 ], the petroleum industry [ 70 ], commercial aviation [ 71 ], education [ 72 ], safety and health [ 73 , 74 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Yuan et al (2011) concluded that SEM is a widespread and well-known method used to analyze data from the social sciences. The SEM analysis approach has been applied in a wide variety of fields in the past, such as organization cultural differences (Ali et al, 2019), safety management (Ajmal et al, 2022;Al-Mekhlafi et al, 2021), waste management (Mohammed et al, 2022;Mohammed et al, 2021), online education (Al-Mekhlafi et al, 2022). As a result, the partial least square PLS-SEM method has been used to assess corporate reputation's influence on turnover intention.…”
Section: Approach Of the Analysis Structured Equation Modeling Pls-semmentioning
confidence: 99%
“…The main goal of safety management is to prevent workplace injuries, illnesses, and deaths, as well as the suffering and financial hardships of the organizations [ 34 ]. The recommended practices use a proactive approach to managing workplace safety and health, instead of using the reactive ones, i.e., problems are addressed only after a worker is injured or becomes sick.…”
Section: Literature Reviewmentioning
confidence: 99%